Exploitation of Women in the Novel Bumi Manusia By Pramoedya Ananta Toer - Lilik Herawati; Agus Nuryatin; Teguh Supriyanto; Mukh Doyin (Universitas Negeri Semarang, 2023)
The relationship between men and women is often described in literary works. Women often experience various forms of exploitation. Research that examines problems from a women's perspective with the aim of showing that men and women are treated differently is one of the goals of feminist studies. This research is expected to be able to describe the depiction of exploitation of women in the novel Bumi Manusia by Pramoedya Ananta Toer. As previously mentioned, this study aims to explain how patriarchal culture depicts the exploitation of women and how this can harm women. This study uses a qualitative descriptive method by utilizing quotations from the novel which is used as the data source, namely the Bumi Manusia Novel by Pramoedya Ananta Toer. The instruments used in exploring the double-dealing of ladies in the original Human Earth involve real scientists as the instruments, because specialists are information gatherers and information analyzers assisted by information cards. The results of the analysis reveal that the novel Bumi Manusia by Pramoedya Ananta Toer contains the ideology of postcolonial feminism with the aim of reconstructing the position of women.